2020
DOI: 10.1177/0892020620963112
|View full text |Cite
|
Sign up to set email alerts
|

The impact of generative school leadership on student performance: The case of Saudi Arabia

Abstract: The primary aim of this study is to facilitate interactions among the generative school leadership of high school principals in Riyadh, Saudi Arabia, to take responsibility for student performance. Existing research suggests that generative leadership is based on the principles of inclusiveness, employee creativity, knowledge transfer and delegation. The sample is based from nine principals from large high schools. To investigate this issue, this qualitative study assesses and analyses interviews and comments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…A growing body of literature on collaborative leadership has been published in the KSA over the last few years, and this paper provides a brief overview of the research published on this topic. The Saudi Arabian educational sector has been reported to be highly centralised and traditionalist, adversely affecting creativity and inclusivity and, as a result, negatively impacting students' performance as a result (Albeladi, 2016;Alghulayqah, 2022). Al-Mutairi (2015) found that secondary school principals practice collaborative leadership to a moderate level in their schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing body of literature on collaborative leadership has been published in the KSA over the last few years, and this paper provides a brief overview of the research published on this topic. The Saudi Arabian educational sector has been reported to be highly centralised and traditionalist, adversely affecting creativity and inclusivity and, as a result, negatively impacting students' performance as a result (Albeladi, 2016;Alghulayqah, 2022). Al-Mutairi (2015) found that secondary school principals practice collaborative leadership to a moderate level in their schools.…”
Section: Literature Reviewmentioning
confidence: 99%